SUBCLINICAL LESION OF CAROTID ARTERIES IN CHRONIC GLOMERULONEPHRITIS - I. T. Murkamilov; R. A. Aitbaev; V. V. Fomin; F. A. Yusupov (Архивъ внутренней медицины)
Purpose of the study. Examine gender characteristics of lesion of precerebral arteries and their relationship with renal dysfunction in patients with chronic glomerulonephritis at predialysis stage of the disease.Material and methods.The study included 306 patients with chronic glomerulonephritis aged 17 to 71 years. Group 1 — male (n = 210), group 2 — women (n = 96). All patients, in addition to general clinical testing methods, had noninvasive assessment of structural changes in precerebral arteries. Results and conclusion. In patients with chronic glomerulonephritis, structural changes in precerebral arteries are detected at predialysis stage and do not showsignificant difference depending on gender. Male individuals hadhypoproteinemia, subnephrotic proteinuria, clinically relevant hypertriglyceridemia and higher rates of precerebral arteries’ thickness, compared to female patients. At the same time, female individuals showed significantly worse parameters of peripheral blood and renal function, compared to male patients. Negative correlation between glomerular filtration rate and thickness of common and internal carotid artery was found both in general group and in individual male group. The results of the study suggest that in order to prevent vascular complications in the future, patients with chronic glomerulonephritis on the pre-dialysis stage of CKD need to study carotid arteries, as well as in a comprehensive analysis of renal function